Ukrainian Citizens’ Attitudes towards Surzhyk in Times of Russian Aggression - Levchuk, Paweł (Wiener Slawistischer Almanach, 2024)
The article explores the emotional attitudes of people living in Ukraine toward Surzhyk, the Ukrainian-Russian mixed code. An online survey was conducted in which respondents were asked to give their reactions to predefined statements that embody attitudes toward Surzhyk ranging from negative to neutral to positive. Some respondents provided additional comments, expressing in a more nuanced way their opinions on Surzhyk. Our findings represent the culmination of research on attitudes toward Surzhyk since the onset of Russian aggression in Ukraine in 2022.